A conserved cellular mechanism for cotton fibre diameter and length control. Issue 1 (14th April 2022) - Yanagisawa, Makato; Keynia, Sedighe; Belteton, Samuel; Turner, Joseph A; Szymanski, Daniel
Abstract: Highly polarized cotton fibre cells that develop from the seed coat surface are the foundation of a multi-billion-dollar international textile industry. The unicellular trichoblast emerges as a hemispherical bulge that is efficiently converted to a narrower and elongated shape that extends for about 2 weeks before transitioning into a cellulose-generating machine. The polarized elongation phase employs an evolutionarily conserved microtubule-cellulose synthase control module that patterns the cell wall and enables highly anisotropic diffuse growth. As the multi-scale interactions and feedback controls among cytoskeletal systems, morphologically potent cell wall properties, and a changing cell geometry are uncovered, opportunities emerge to engineer architectural traits. However, in cotton, such efforts are hampered by insufficient knowledge about the underlying control mechanisms. For example, fibre diameter is an important trait that is determined during the earliest stages of development, but the basic growth mode and the mechanisms by which cytoskeletal and cell wall systems mediate fibre tapering are not known. This paper combines multiparametric and multiscale fibre phenotyping and finite element computational modelling of a growing cell to discover an evolutionarily conserved tapering mechanism. The actin network interconverts between two distinct longitudinal organizations that broadly distributes organelles and likely enables matrix secretion patterns that maintain cell wall thickness during growth. Based on plausible finite element models and quantitative analyses of the microtubule cytoskeleton, tapering and anisotropic growth is programmed by a constricting apical microtubule depletion zone and highly aligned microtubules along the fibre shaft. The finite element model points to a central role for tensile forces in the cell wall to dictate the densities and orientations of morphologically potent microtubules that pattern the cell wall.